Be careful what you wish for - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- Clifton chronicles, 2014)
When Ross Buchanan is forced to resign as chairman of the Barrington Shipping Company, Emma Clifton wants to take his place, but Don Pedro Martinez plans to install his puppet, the egregious Major Alex Fisher, so he can destroy the Barrington family firm once and for all. The talented Jessica Clifton, Harry and Emma's adopted daughter, wins a scholarship to the Slade Academy of Art and falls in love with a fellow student, Clive Bingham, who asks her to marry him. Both families are delighted and preparations for the nuptials are well under way, when Charlotte Bingham, Jessica's future mother-in-law, has a visit from an old friend, Lady Virginia Fenwick, who drops her particular brand of poison into the wedding chalice. But then, without warning, a man no one had ever heard of takes his place on the board of Barringtons and causes an upheaval that none of them could have anticipated. Cedric Hardcastle, a bluff Yorkshire banker, quickly decides who he should support, Emma Clifton or Don Pedro Martinez, and the story takes yet another twist.